Development of fibre-rich okara-based expanded snack via single screw extrusion - L., Nur Adibah; M., Nor Afizah; W. I., Wan Zunairah; S. K., Syed Muhammad (Rynnye Lyan Resources, 2024)
Okara is a by-product of the soymilk and tofu manufacturing industry. Recently, changes in lifestyle and eating patterns led to higher demands for snack foods produced via extrusion technology. Extruded products enriched with okara, which consists of high dietary fibre content, can increase the nutritional quality of extruded snacks with higher commercial values. This study aimed to determine the influence of okara levels; 0, 5, 10, and 15% (w/w) on properties of extrudates in terms of fibre content, water activity, bulk density, expansion ratio, colour, textural (hardness and crispness), and microstructure. The increment of okara level resulted in the reduction of water activity, expansion ratio, lightness, and crispness of extrudates while, soluble and insoluble dietary fibre content, bulk density, and hardness were increased. Extrudate produced at higher levels of okara had a rougher surface, smaller air cells, and thicker walls. A collapse in cell structure was observed at 15% okara. In conclusion, fibre-enriched extrudate with desirable characteristics can be obtained at a 5% okara level. This study provides a promising application in harnessing the nutritional benefits of okara.